1999
DOI: 10.1007/pl00006798
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Mice with Yersinia enterocolitica Serotype O9 by Oral and Parenteral Routes: Spreading and Enterotropism of Virulent Yersiniae

Abstract: An isogenic pair of Yersinia enterocolitica serotype O9 strains, with and without virulence plasmid, was used to study the plasmid role in the infection of BALB/c mice by oral, intraperitoneal, and intravenous routes. The plasmid-bearing strain, but not its plasmid-less derivative, caused enteric infection after challenge by all three routes. The virulence plasmid did not influence the peritoneal clearance of yersiniae, but only the plasmid-bearing yersiniae were able to move from the peritoneal cavity to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Therefore, an inflammatory reaction to bacterial components may be involved in splenomegaly development. However, in our assays, spleens from 10-d-infected mice were sterile, although recovery of yersiniae from faeces was always demonstrated (data not shown) ; this is in agreement with our previous description of the experimental infection of BALB\c mice with Y. enterocolitica O9 (Ruiz-Bravo et al, 1999).…”
Section: Effects Of Y Enterocolitica Infection On Splenic Cell Phenosupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, an inflammatory reaction to bacterial components may be involved in splenomegaly development. However, in our assays, spleens from 10-d-infected mice were sterile, although recovery of yersiniae from faeces was always demonstrated (data not shown) ; this is in agreement with our previous description of the experimental infection of BALB\c mice with Y. enterocolitica O9 (Ruiz-Bravo et al, 1999).…”
Section: Effects Of Y Enterocolitica Infection On Splenic Cell Phenosupporting
confidence: 93%
“…Therefore, an inflammatory reaction to bacterial components may be involved in splenomegaly development. However, in our assays, spleens from 10-d-infected mice were sterile, although recovery of yersiniae from faeces was always demonstrated (data not shown) ; this is in agreement with our previous description of the experimental infection of BALB\c mice with Y. enterocolitica O9 (Ruiz-Bravo et al, 1999).Flow cytometry analysis of spleen cells revealed that the absolute numbers of CD3 + total T cells, CD4 + helper T cells, CD8 + cytotoxic T cells and CD11b + phagocytic cells were significantly increased (1n7-fold, P 0n05 ; 1n4-fold, P 0n025 ; 1n7-fold, P 0n04 ; and 5n6-fold, P 0n04, respectively) in 10-d-infected animals (Fig. 1).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Dissemination of L. monocytogenes after morphine administration in BALB/c mice. Mice were infected with 6.1ϫ10while others, including diarrheagenic E. coli, S. flexneri, Y. enterocolitica, are not capable of establishing systemic infection in the mice model via intraperitoneal infection and are immediately excreted from the mice when infected via oral or intraperitoneal routes (22). However, it was reported that morphine caused the systemic dissemination of other extracellular bacteria such as Klebsiella pneumoniae, and Streptococcus pneumoniae when these pathogens were intranasally inoculated to cause lethal infection even in the untreated mice (25,27).…”
mentioning
confidence: 99%